Cultural differences in body dissatisfaction: Japanese adolescents compared with adolescents from China, Malaysia, Australia, Tonga, and Fiji. Issue 4 (October 2016) - Brockhoff, Miki; Mussap, Alexander J.; Fuller‐Tyszkiewicz, Matthew; Mellor, David; Skouteris, Helen; McCabe, Marita P.; Ricciardelli, Lina A.
Abstract : Cultural influences on the body image of 133 female and 99 male Japanese adolescents aged 12–18 years (M = 15.9, SD = 1.2) were compared to those of a databank of 1233 female and 1149 male adolescents also aged 12–18 years (M = 14.9, SD = 1.5) from five cultures – Chinese, Malaysian, Australian, Tongan, and indigenous Fijian – surveyed previously using identical body image measures (Fuller‐Tyszkiewicz et al., 2012). Japanese adolescents reported the highest levels of body dissatisfaction despite possessing among the lowest body mass index (BMI) and also reported among the highest levels of media influence on their body image. Subsequent path analyses revealed that for Japanese adolescents cultural identification with modern Japanese values were associated with increased body dissatisfaction, and that this association was mediated by level of media influence. These results highlight the importance of cultural influences, as well as individual differences in cultural values, in shaping Japanese adolescents' body image.